The Influence of Family-Based Assistance and Counseling on the Acceleration of Reducing Stunting among Toddlers in Medan Sungal Subdistrict in 2023 - Marliani, Marliani; Dewi, Eva Ratna; Wahyuni, Retno; Manurung, Herna Rinayanti; Tobing, Rati Aksari Lumban; Gultom, Ester Junita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Accelerated reduction in stunting starts from the preconception period to the first 1,000 days of life. Teenagers, prospective brides/pUS candidates, pregnant women, breastfeeding mothers and children aged 0-59 months. Mentoring and counseling can contribute to increasing knowledge, attitudes and actions of families in preventing stunting. The problem of this research is what the effect of mentoring and counseling in families on accelerating the reduction of stunting in toddlers. The aim of this research is to determine the effect of family assistance and counseling on accelerating the reduction of stunting in toddlers. The urgency of this research is considered very high because it can be the basis for preparing a Government program to accelerate the reduction of stunting, the number of which is still very large, especially in Medan Sunggal Subdistrict. The mandatory output of this research is articles published in accredited journals 1-6. Additional output is publications in international journals and monographs. The level of technology readiness (TKT) resulting from this research is in the form of a report on family-based assistance and counseling to accelerate the reduction of stunting in toddlers in Medan Sunggal Village (until TKT 2). The achievements of TKT 1 are the study of scientific literature on the basic principles of technology (100%), an initial market survey has been initiated and assessed (100%), the potential for scientific applications for problem solving (100%). TKT 2 achievements are: Hypothesis has been formed (100%), research design development is in place (100%), research protocol (80%), and protocol has been reviewed by experts (80%) and so on.